1982
DOI: 10.1111/j.1440-1819.1982.tb00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Degeneration in the Lateral Septum of the Rat after Suprachiasmatic Nucleus Lesion

Abstract: Nerve terminals in the lateral septum were studied by electron microscopy in the rat after lesions of the suprachiasmatic nuclei (SCN). The results were as follows: 1) The electron‐lucent degenerations showed a reduction in the number of vesicles and the swelling of terminals and/or vesicles. These degenerating terminals predominated at two days of survival period. The electron‐dense degenerations which showed a darkening and shrinkage of the terminals mainly appeared at four days of survival period. 2) Most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Mice are nocturnal animals. 32 The lateral septum has close connections with multiple brain regions associated with biologic rhythm cycles, such as the suprachiasmatic nucleus, 33,34 supraoptic nucleus, 28 and paraventricular nucleus. 35 In line with this, we found that c-Fos expression in the lateral septum was higher during nighttime than during daytime.…”
Section: Discussionmentioning
confidence: 99%
“…Mice are nocturnal animals. 32 The lateral septum has close connections with multiple brain regions associated with biologic rhythm cycles, such as the suprachiasmatic nucleus, 33,34 supraoptic nucleus, 28 and paraventricular nucleus. 35 In line with this, we found that c-Fos expression in the lateral septum was higher during nighttime than during daytime.…”
Section: Discussionmentioning
confidence: 99%